2020
DOI: 10.1021/acsami.0c10869
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetime-Tunable Water-Resistant Perovskite Quantum Dots for Multidimensional Encryption

Abstract: Using temporal dimension in optical multiplexing is a promising method to increase the security of data encryption. However, adjusting the fluorescence lifetime of light-emitting material often results in inevitable changes in their fluorescence spectra, which is unfavorable for confidential information protection. Here, we report the preparation of various perovskite quantum dot/polymer nanospheres (PQD/polymer) with tunable and long fluorescence lifetimes but identical fluorescence spectra, which are ideal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…The record of photoluminescence and electroluminescence efficiency 216 of 2D perovskites has continuously been broken in display, encryption, biological imaging and X-Ray detection. 52,217,218 For instance, Chandra et al 219 reported the use of specific antibody attached water-resistant CsPbBr 3 nanocrystals in different dimensions for two-photon imaging of breast cancer cells in the near IR region, superior to conventional organic fluorescence labels.…”
Section: Perspectivesmentioning
confidence: 99%
“…The record of photoluminescence and electroluminescence efficiency 216 of 2D perovskites has continuously been broken in display, encryption, biological imaging and X-Ray detection. 52,217,218 For instance, Chandra et al 219 reported the use of specific antibody attached water-resistant CsPbBr 3 nanocrystals in different dimensions for two-photon imaging of breast cancer cells in the near IR region, superior to conventional organic fluorescence labels.…”
Section: Perspectivesmentioning
confidence: 99%
“…The fast‐decay component (τ 1 ) can be attributed to exciton recombination in the interior crystal, and the slow‐decay component (τ 2 ) can be attributed to the trap‐mediated exciton recombination. [ 46,47 ] As shown in Table S3, Supporting Information, τ 1 is ≈4–7 ns for the samples, and it is very close to that of colloid PQDs and shorter than that of PQDs in glass generated by traditional heat treatment, which confirms the high quality of interior crystals in the PQDs generated by ultrafast laser direct writing. [ 48–51 ] An increase in RF from 50 to 100 kHz results in a slight decrease in average lifetime τ ave with the proportion of τ 1 (τ 2 ) decreases (increases).…”
Section: Resultsmentioning
confidence: 64%
“…To overcome the instability problem, several strategies were proposed, including doping (Liu et al, 2017), inorganic shell (Wang et al, 2018;Dirin et al, 2019), ligand passivation (Zhang et al, 2019;Lu et al, 2021;Min et al, 2022), polymer matrix (Liu et al, 2020b). Liu et al (2017) doped the aluminum into perovskite quantum dots and fabricated the white LED that displays 116% NTSC.…”
Section: The Properties Of Perovskite Quantum Dotsmentioning
confidence: 99%